Spectral and temporal characteristics of target current and electromagnetic pulse induced by nanosecond laser ablation. (28th April 2017) - Krása, J; De Marco, M; Cikhardt, J; Pfeifer, M; Velyhan, A; Klír, D; Řezáč, K; Limpouch, J; Krouský, E; Dostál, J; Ullschmied, J; Dudžák, R
Abstract: The current balancing the target charging and the emission of transient electromagnetic pulses (EMP) driven by the interaction of a focused 1.315 μ m iodine 300 ps PALS laser with metallic and plastic targets were measured with the use of inductive probes. It is experimentally proven that the duration of return target currents and EMPs is much longer than the duration of laser-target interaction. The laser-produced plasma is active after the laser-target interaction. During this phase, the target acts as a virtual cathode and the plasma-target interface expands. A double exponential function is used in order to obtain the temporal characteristics of EMP. The rise time of EMPs fluctuates in the range up to a few tens of nanoseconds. Frequency spectra of EMP and target currents are modified by resonant frequencies of the interaction chamber.